MPC-5 Characteristics of H3 G34-mutant gliomas. (6th December 2021) - Kibe, Yuji; Ohka, Fumiharu; Motomura, Kazuya; Aoki, Kosuke; Maeda, Sachi; Hirano, Masaki; Nishikawa, Tomohide; Yamaguchi, Junya; Yamazaki, Shintaro; Natsume, Atsushi; Saito, Ryuta
Abstract: Introduction: Diffuse hemispheric gliomas, H3 G34-mutant (DHG H3G34-mutant) are newly recognized infiltrating gliomas of the cerebral hemispheres of pediatric and young adult patients. We experienced 6 DHG H3G34-mutant cases. In this study, we describe the clinical, radiological and pathological characteristics of these cases. Result: Mean age at diagnosis was 16.8 years (range:10–26). Three patients were male. Among six cases, tumors located in cerebral cortex in five cases and multiple sites including basal ganglia and cortex in a case. All tumors showed no or only a faint contrast-enhancement and harbored restriction of diffusion. One patient underwent total resection, four underwent partial resection and one underwent biopsy. Pathological diagnosis were CNS embryonal tumors (n=3/6), glioblastoma, IDH-wildtype (n=2/6) and anaplastic astrocytoma, IDH-wildtype (n=1/5). All cases were negative for Olig2 and positive for GFAP in immunohistochemistry. Mean Ki-67 index was 38% (range: 10–60%). All cases revealed at least one of mitosis, necrosis or microvascular proliferation. Especially, mitosis was the most frequently found (n=5/6). The H3F3A mutations were G34R mutations in all cases. One case revealed a characteristic mutation pattern, therefore now we are performing further examination. Adjuvant chemoradiotherapies were performed for all cases. Mean progression free survival was 10.1 months (range: 1.6–33.1). Discussion: As published literatures reported, all cases exhibited restriction of diffusion and negative for Olig2. For a cerebral hemispheric tumor of pediatric or young adult patient which shows restriction of diffusion and no contrast-enhancement, and of which pathological findings is malignant and olig2 is negative, genetic analysis of H3F3A gene might be essential.